Evaluación de la calidad de agua en los ríos, Sicalpa y Llin-Llin, del Cantón Colta, mediante el uso de los índices ICA, BMWP y ABI. - Carrillo Veintimilla, Olga María (2025)
The objective of this study was to evaluate water quality in the Sicalpa and Llin-Llin rivers of the Colta canton, Chimborazo province, using the ICA, BMWP, and ABI indices. Ten sampling points were established in each micro-watershed, distributed according to land use coverage and accessibility. Water samples were collected at each sampling point to determine physicochemical and microbiological parameters. A D-net was used to collect benthic macroinvertebrates. Regarding benthic macroinvertebrates, the Sicalpa River micro watershed recorded a total of 3,364 individuals distributed across 19 families and 7 orders, while the Llin-Llin River micro-watershed recorded 8,684 individuals distributed across 26 families and 9 orders. The combination of tolerant and sensitive families allows for inferring pollution gradients and changes in habitat structure, providing key information on the ecosystem's health. Water quality indices (ICA, BMWP, and ABI) in the Sicalpa and Llin Llin micro-basins indicate that both bodies of water are of questionable to good quality. The ICA results indicate water quality ranging from fair to poor, while the BMWP and ABI indices reveal significant ecological deterioration, reflected in the decline of pollution sensitive macroinvertebrates. Overall, the results reveal increased environmental pressure on the Sicalpa River and improved ecological status in the Llin-Llin River. This variability in the results demonstrates that human activities in the micro-basins are becoming a threat to the stability of high Andean ecosystems.